If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2r + 8(2 + 8r) + -182 = 0 2r + (2 * 8 + 8r * 8) + -182 = 0 2r + (16 + 64r) + -182 = 0 Reorder the terms: 16 + -182 + 2r + 64r = 0 Combine like terms: 16 + -182 = -166 -166 + 2r + 64r = 0 Combine like terms: 2r + 64r = 66r -166 + 66r = 0 Solving -166 + 66r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '166' to each side of the equation. -166 + 166 + 66r = 0 + 166 Combine like terms: -166 + 166 = 0 0 + 66r = 0 + 166 66r = 0 + 166 Combine like terms: 0 + 166 = 166 66r = 166 Divide each side by '66'. r = 2.515151515 Simplifying r = 2.515151515
| 1/4g+2/3G= | | -4(2-3x)=7-3(x-3) | | x+5+3x+6+7x-3=-14 | | -3(3+x)+4(x+6)=-4 | | -1/3x-1/2=1/4x-1 | | 23/7-11c/7=5c | | (-46)+(1)= | | 111-6(3n-7)-3= | | -6.3x+6=x-8.4 | | -12x-18=+6-7x | | 6+0.1.x=0.15x+8 | | M/2-4=9 | | (3x^6y^2)(6xy^2)=0 | | 6n+7=-49 | | g-12.23=10.6 | | -123-3(6x+1)= | | 1/3x-1/2=1/4-1 | | (4x^2y^2)(6xy^2)=0 | | 3x+82x+x+6+1=-3 | | 2(1+6p)-82= | | 3(3+k)=-6 | | 6x-23=x-5+(3x+2) | | 355-9x=299+12x | | 8(10+n)=72 | | 6=x-3y | | 12-9x-10=22+3 | | -2-7(1-4x)-149= | | 10p+3=-97 | | -18=1/4x-15 | | 1h+11=8 | | 6.4+2.1(z-2)=8.6 | | 10=4-x |